G673 could be a novel mutational hot spot for intragenic suppressors of pheS5 lesion in Escherichia coli. Issue 3 (8th May 2014) - Ponmani, Thangaraj; Munavar, M. Hussain
Abstract The pheS5 Ts mutant of Escherichia coli defined by a G293 → A293 transition, which is responsible for thermosensitive Phenylalanyl‐tRNA synthetase has been well studied at both biochemical and molecular level but genetic analyses pertaining to suppressors of pheS5 were hard to come by. Here we have systematically analyzed a spectrum of Temperature‐insensitive derivatives isolated from pheS5 Ts mutant and identified two intragenic suppressors affecting the same base pair coordinate G673 (pheS19 defines G673 → T673; Gly225 → Cys225 and pheS28 defines G673 → C673; Gly225 → Arg225). In fact in the third derivative, the intragenic suppressor originally named pheS43 (G673 → C673transversion) is virtually same as pheS28. In the fourth case, the very pheS5 lesion itself has got changed from A293 → T293 (named pheS40). Cloning of pheS+, pheS5, pheS5‐pheS19, pheS5‐pheS28 alleles into pBR322 and introduction of these clones into pheS5 mutant revealed that excess of double mutant protein is not at all good for the survival of cells at 42°C. These results clearly indicate a pivotal role for Gly225 in the structural/functional integrity of alpha subunit of E. coli PheRS enzyme and it is proposed that G673 might define a hot spot for intragenic suppressors of pheS5.